Reappraise the Situation but Express Your Emotions: Impact of Emotion Regulation Strategies on ad libitum Food Intake - Taut, Diana; Renner, Britta; Baban, Adriana (Frontiers in Psychology, 2012)
Research investigating the role of maladaptive emotion regulation on food intake has exclusively focused on food intake in a forced consumption situation. In contrast, the present study examined the effect of negative emotions (fear, negative affect) and emotion regulation strategies (suppression, reappraisal) on food intake in a non-forced, free eating setting where participants (N = 165) could choose whether and how much they ate. This free (ad libitum) eating approach enabled, for the first time, the testing of 1) whether eating (yes/no) is used as a secondary emotion regulation strategy and 2) whether the amount of food intake differed, depending on the emotion regulation strategy. In order to produce a more ecologically valid design, emotion regulation strategy manipulation was realized while exposing participants to emotion-induction procedures. To induce an initial negative emotional state, a movie clip was presented without emotion regulation instruction. The instructions to regulate emotions (suppression, reappraisal, no emotion regulation instruction) then preceded a second clip. The results show that whereas about two-thirds of the control (no emotion regulation instruction) and suppression groups began to eat, only one-third of the reappraisal group did. However, when reappraisers began to eat, they ate as much as participants in the suppression and control groups. Accordingly, the results suggest that when people are confronted with a negative event, eating is used as a secondary coping strategy when the enacted emotion regulation is ineffective. Conversely, an adaptive emotion regulation such as reappraisal decreases the likelihood of eating in the first place, even when emotion regulation is employed during rather than before the unfolding of the negative event. Consequently, the way we deal with negative emotions might be more relevant for explaining emotional eating than the distress itself.